Dark circles : a novel - Dolan-Leach, Caite (Ballantine Group, 2022)
"Olivia Reed needed a break. She doesn't want to think about her name plastered on tabloids or be reminded of her recent meltdown on a Manhattan street. Her micromanaging publicist has just the thing in mind: A remote retreat in Upstate New York-the House of Light. It's not rehab; it's a spiritual center, a site for seeking realignment and personal growth. There will be yoga and morning meditation, soft bamboo-blend fabrics and crystals to snuggle. But Liv will soon find that the House of Light is filled with darkness. She is approached by a prickly local, Ava, who informs her that something twisted is lurking beneath the the Light's veneer. There have been a series of mysterious suicides committed by women caught in the Light's web, and no matter who Ava talks to, no one believes her. To get the truth out and put her celebrity to good use, Liv starts a podcast, dodging flashlight beams to record at Ava's home and seeking to connect the dots and expose the Light's true intentions, if she and Ava can find them. Beneath the glowing skin of the Light's inhabitants are rotten souls, and Liv learns that she can trust no one-except herself."--